A comparison of two calibration techniques for large volume calibration - Becker, J.; Howell, D.; Chou, L. S. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to compare results produced using two different large volume calibration techniques with those produced by using an optical motion capture system. A volume measuring 2.5x8x2 m. was calibrated using 4 survey poles, a multiphase calibration, and with a motion capture system. Reconstructions using the survey poles and multiphase calibration technique produced similar movement patterns as the motion capture system for both the position of a single marker and for tracking the whole body center of mass (COM). The multiphase calibration resulted in larger DLT errors for reconstruction of the control points, however, compared to the motion capture system, it also resulted in smaller RMS differences for both a single marker and for the COM.